Case report: A case of intravascular large B-cell lymphoma and related literature review - Zhou, Wen; Guo, Xiaojia; Liu, Yang; Wang, Xin; Zhang, Hongbin; Zhang, Liansheng; Li, Lijuan (Frontiers in Hematology, 2025)
Intravascular large B-cell lymphoma (IVLBCL) presents with a wide range of clinical symptoms, making clinical diagnosis challenging. It is often misdiagnosed or overlooked, leading to delays in treatment for affected patients. We present a case of a patient exhibiting clinical symptoms such as chest tightness, dyspnea, fever, and edema, who was later diagnosed with secondary hemophagocytic syndrome (HPS). Laboratory tests indicated persistent hypoalbuminemia, significantly elevated lactate dehydrogenase levels, thrombocytopenia, and splenomegaly, with no evidence of lymphadenopathy. During the treatment for HPS, the patient developed a rash on both lower limbs and abdomen and was ultimately diagnosed as IVLBCL after a skin biopsy. Following four cycles of zanubrutinib in combination with the R-CHOP regimen (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone), the patient achieved complete resolution of both dermatological manifestations and systemic symptoms. Laboratory parameters, including complete blood count, serum albumin levels, and lactate dehydrogenase, were normalized. Additionally, ultrasonography demonstrated a marked reduction in splenic size. However, the patient exhibited suboptimal adherence to the prescribed treatment plan and did not complete the intended number of cycles. During a subsequent telephone follow-up, the patient was confirmed to be alive; however, the status of the disease could not be evaluated. As of the latest follow-up, the patient has survived for 2 years.